2011
DOI: 10.1155/2011/658569
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Aged Residues of Atrazine and Alachlor in a Mix-Load Site Soil by Fungal Enzymes

Abstract: Soils from bulk pesticide mixing and loading (mix-load) sites are often contaminated with a complex mixture of pesticides, herbicides, and other organic compounds used in pesticide formulations that limits the success of remediation efforts. Therefore, there is a need to find remediation strategies that can successfully clean up these mix-load site soils. This paper examined the degradation of atrazine (2-chloro-4-ethylamino-6-isopropylamino-S-triazine; AT) and alachlor (2-chloro-2 , 6 -diethyl-N-[methoxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…Complete mineralization is the most favorable way of biodegradation; however, the vast majority of the xenobiotics biodegradation pathways (including triazines) end in the formation of by-products. Formation of ametryn metabolites during the experiments presented in this work is partially in agreement with the reactions of atrazine biodegradation, where the formation 2-hydroxyatrazine has been observed in many species (Atrazine Pathway Map, 2017; KEGG Atrazine degradation -Reference pathway, 2017; Govantes et al, 2009;Solomon et al, 2013;Abigail et al, 2013), while deethylation of ethanamine substituents seems to be characteristic for fungal strains and mammals (Chirnside et al, 2011;Pereira et al, 2013, Sciali et al, 2014. Figure 6.…”
Section: Discussionsupporting
confidence: 86%
“…Complete mineralization is the most favorable way of biodegradation; however, the vast majority of the xenobiotics biodegradation pathways (including triazines) end in the formation of by-products. Formation of ametryn metabolites during the experiments presented in this work is partially in agreement with the reactions of atrazine biodegradation, where the formation 2-hydroxyatrazine has been observed in many species (Atrazine Pathway Map, 2017; KEGG Atrazine degradation -Reference pathway, 2017; Govantes et al, 2009;Solomon et al, 2013;Abigail et al, 2013), while deethylation of ethanamine substituents seems to be characteristic for fungal strains and mammals (Chirnside et al, 2011;Pereira et al, 2013, Sciali et al, 2014. Figure 6.…”
Section: Discussionsupporting
confidence: 86%
“…Past studies showed that the presence of additional substrates could initiate cometabolism of the desired compounds [15]. Bacteria and fungi can degrade alachlor through cometabolism [20,23,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two percent of atrazine and 54% of alachlor were degraded in the biometers using white rot fungus, Phanerochaete chrysosporium . The half-life for atrazine and alachlor was 8.0 and 3.0 days, respectively [23]. Ninety-nine percent of alachlor degradation was achieved in anoxic slurries of corn-cultivated soil due to the preexistence of microorganisms in the soil [24].…”
Section: Introductionmentioning
confidence: 99%
“…Most developed countries stopped using these pesticides after imposition of ban but developing or underdeveloped countries could not due to lack of policy [3]. White rot fungi (Basidiomycetes:Xylariaceae) are popular among all fungi as these can tolerate high concentration of pesticides from mix-load sites [4]. Several isolates of white rot fungi have been used since 1985 for biodegradation of OCPs.…”
Section: Introductionmentioning
confidence: 99%